Structural Influence on the Dominance of Virus-Specific CD4 T Cell Epitopes in Zika Virus Infection - Koblischke, Maximilian; Stiasny, Karin; Aberle, Stephan W.; Malafa, Stefan; Tsouchnikas, Georgios; Schwaiger, Julia; Kundi, Michael; Heinz, Franz X.; Aberle, Judith H. (Frontiers in Immunology, 2018)
Zika virus has recently caused explosive outbreaks in Pacific islands, South- and Central America. Like with other flaviviruses, protective immunity is strongly dependent on potently neutralizing antibodies directed against the viral envelope protein E. Such antibody formation is promoted by CD4 T cells through direct interaction with B cells that present epitopes derived from E or other structural proteins of the virus. Here we examined the extent and epitope dominance of CD4 T cell responses to capsid (C) and envelope proteins in Zika patients. All patients developed Zika virus-specific CD4 T cell responses, with substantial contributions of C and E. In both proteins, immunodominant epitopes clustered at sites that are structurally conserved among flaviviruses but have highly variable sequences, suggesting a strong impact of protein structural features on immunodominant CD4 T cell responses. Our data are particularly relevant for designing flavivirus vaccines and their evaluation in T cell assays and provide insights into the importance of viral protein structure for epitope selection and antigenicity.